HUBUNGAN PENGETAHUAN, UMUR DAN PENDIDIKAN AKSEPTOR KB DENGAN PENGGUNAAN ALAT KONTRASEPSI DALAM RAHIM (AKDR) DI DESA RAMBAH TENGAH HULU - Eka Yuli Handayani; Rahmi Fitria (Institut Kesehatan dan Teknologi Al Insyirah, 2022)
The Intrauterine Contraceptive Device (IUD), is a small, sylastic, contraceptive device with an arm or copper wire around it that is placed in the uterus that provides long-term protection against pregnancy. The IUD is a safe, effective, and convenient contraceptive option for many women. The IUD only requires one insertion which can be used for a long period of time at a relatively low cost, high effectiveness, low failure rate, 0.6 ± 0.8 pregnancies/100 women in the first year of use. This study aims to determine the relationship of knowledge, age, and education of family planning acceptors to the selection of intrauterine contraceptive devices (IUD) in Rambah Tengah Hulu Village, Rambah District, Rokan Hulu Regency. The type of research used for this research is quantitative research with cross sectional design. The population in this study were all family planning acceptors in the village of Rambah Tengah Hulu, Rambah District, Rokan Hulu Regency totaling 289 people with a sample of 74 people. The sampling technique used was incidental sampling. The data analysis used was univariate and bivariate analysis using analysis Chi-square. From the results of the study, there was a significant relationship between knowledge (P-value 0.001), age (P-value 0.001), and education (P-value 0.004) on IUD use. It is necessary to conduct counseling in Rambah Tengah Hulu Village, Rambah District, Rokan Hulu Regency, to increase respondents' knowledge about the IUD.